Investigations on Mechanical and Metallurgical Properties of Pulsed GTA Welded Maraging Steel C300. (2018) - Arivarasu, M.; Manikandan, M.; Jualeash, M.J.; Deepak, P.; Padmanaban, R.; Arivazhagan, N.
Abstract: This article presents the weldability of maraging steel C300 by pulsed current gas tungsten arc welding. Successful full penetration, defect free weld joint between C300 plates were obtained without employing any filer wire. The weldments were characterised for metallurgical and mechanical properties and an attempt is made to correlate the structure property relation between them. The optical microscopic and SEM microstructures revealed the variation of structure across the weldment. A line mapping analysis carried out across the weldment using energy dispersive spectroscopy revealed the varying elemental composition across the weldment. The retained austenite formed at the fusion zone and the elemental migration during the welding played a major role in altering the mechanical property of the weldment.